The Polymorphism in Various Milk Protein Genes in Polish Holstein-Friesian Dairy Cattle - Kolenda, Magdalena (Animals (Basel), 2021)
SIMPLE SUMMARY: The aim of the present study was to evaluate the genetic variability within casein alpha S1 (CSN1S1), casein alpha S2 (CSN1S2), beta-casein (CSN2), kappa-casein (CSN3), and progestagen-associated endometrial protein (PAEP) genes. The study was conducted on 1900 Polish Black and White Holstein-Friesian dairy cows that were genotyped using customized EuroGenomics microarrays. Out of investigated 24 genetic variants within four genes coding milk protein, 16 expressed genetic diversity. The fact that many of the investigated Single Nucleotide Polymorphisms (SNPs) were monomorphic may suggest that in the past the reproduction program favored one of these genotypes. Populations of high-yielding cows become more and more even and similar in terms of genotype, which may have an adverse effect in future breeding, therefore, the variability in genetic variants of genes coding milk protein should be monitored. ABSTRACT: The aim of the present study was to evaluate the genotype and allele frequencies of 24 polymorphisms in casein alpha S1 (CSN1S1), casein alpha S2 (CSN1S2), beta-casein (CSN2), kappa-casein (CSN3), and progestagen-associated endometrial protein (PAEP) genes. The study included 1900 Polish Black and White Holstein-Friesian dairy cows that were subjected to genotyping via microarrays. A total of 24 SNPs (Single Nucleotide Polymorphisms) within tested genes were investigated. Two CSN1S1 SNPs were monomorphic, while allele CSN1S1_3*G in CSN1S1_3 SNP dominated with a frequency of 99.39%. Out of seven CSN2 SNPs, four were polymorphic; however, only for CSN2_3 all three genotypes were detected. Only three out of nine SNPs within CSN3 were monomorphic. Three PAEP SNPs were also found to be polymorphic with heterozygotes being most frequent. Hardy–Weinberg equilibrium (HWE) was observed for eight variants. It was shown that only CSN3_6 was not in HWE. The fact that many of investigated SNPs were monomorphic may suggest that in the past the reproduction program favored one of these genotypes. SNPs that are included in commercially available microarrays should be monitored in relation to changes in their frequencies. If a SNP has turned monomorphic, maybe it should be considered for removal from the microarray.